Peran Dukungan Sosial Dengan Kompetensi Interpersonal Pada Mahasiswa - Siti Rahmi Qadriyah; Nuristighfari Masri Khaerani; Melisa Paulina; Cholila Shinta Jatisari; Chintia Viranda; Nisa Praditya (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
In this era of globalization, students are required to have competence in developing themselves. This study aims to test whether there is an effect of social support on interpersonal competence in students. Sampling in this study used quota sampling (non-probability sampling) and obtained a sample of 114 students at the Higher Education D.I. Yogyakarta. Data collection techniques using a questionnaire. The reliability of this research instrument uses Cronbach alpha. The interpersonal competency scale consists of 25 items (α= 0.891) and the social support scale consists of 32 items (α= 0.951). The measuring instrument consists of an interpersonal competency scale and a social support scale. Data analysis used linear regression with the help of the SPSS version 21 program. The results showed that there was an influence of social support on interpersonal competence in students. The effective contribution of social support to predict interpersonal competence in students is 15.8% and the remaining 84.2% is influenced by other factors not examined in this study.